2022
DOI: 10.1186/s12934-022-01876-4
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of NTH1 and HSP12 increases the freeze–thaw resistance of baker’s yeast in bread dough

Abstract: Background The intracellular molecule trehalose in Saccharomyces cerevisiae may have a major protective function under extreme environmental conditions. NTH1 is one gene which expresses trehalase to degrade trehalose. Small heat shock protein 12 (HSP12 expressed) plays a role in protecting membranes and enhancing freezing stress tolerance. Results An optimized S. cerevisiae CRISPR-Cpf1 genome-editing system was constructed. Multiplex genome editing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…In a previous study, we observed longer recovery times for colony development after electroporation and higher genome editing efficiency in the CRISPR-Cpf1 system in S. cerevisiae. The efficiency of genome editing is highest at 48 h for cell recovery [27]. However, the curing efficiency did not consistently increase with cell recovery time in this study.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…In a previous study, we observed longer recovery times for colony development after electroporation and higher genome editing efficiency in the CRISPR-Cpf1 system in S. cerevisiae. The efficiency of genome editing is highest at 48 h for cell recovery [27]. However, the curing efficiency did not consistently increase with cell recovery time in this study.…”
Section: Discussioncontrasting
confidence: 59%
“…The S. cerevisiae wild-type strain BCRC 21447 used in this study was obtained from the Bioresource Collection and Research Center. The ∆ade2, ∆nth1, ∆hsp12, and ∆nth1/∆hsp12 strains were constructed from the previous study [26,27]. S. cerevisiae was grown at 30 • C in a YPD medium (1% yeast extract, 2% peptone, and 2% glucose)(BD, Sparks, MD, USA), and 200 mg/L G418 (Sigma-Aldrich, St. Louis, MO, USA) was added for the selection.…”
Section: Strains Media and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…When cells return to a more favourable condition, the accumulated trehalose is hydrolysed into glucose by the trehalase Nth1. Inactivation of NTH1 by mutations, and therefore subsequent impairment of trehalose hydrolysis, can be one of the outcomes of the heat stress response in experimentally evolved strains of S. cerevisiae under high temperature stress 69,70 , suggesting that deficient trehalose hydrolysis can be beneficial under long-term thermal stress conditions. However, NTH1 is generally present in cactophilic genomes, suggesting that absence of NTH1 does not explain impairment in trehalose assimilation in these species.…”
Section: Resultsmentioning
confidence: 99%